Recovery of value-added products from biowaste: A review. (September 2022) - Zhou, Yuwen; Kumar, Vinay; Harirchi, Sharareh; Vigneswaran, V.S.; Rajendran, Karthik; Sharma, Pooja; Wah Tong, Yen; Binod, Parameswaran; Sindhu, Raveendran; Sarsaiya, Surendra; Balakrishnan, Deepanraj; Mofijur, M.; et al.
Graphical abstract: Highlights: Importance of microbial biotechnology for waste utilization is reviewed. Utilization of microbes for lignocelluloses utilization and value-addition are discussed. Importance and possibilities for microbial degradation of plastics are elaborated. Role of microbes in global warming is demonstrated. Abstract: This review provides an update on the state-of-the art technologies for the valorization of solid waste and its mechanism to generate various bio-products. The organic content of these wastes can be easily utilized by the microbes and produce value-added compounds. Microbial fermentation techniques can be utilized for developing waste biorefinery processes. The utilization of lignocellulosic and plastics wastes for the generation of carbon sources for microbial utilization after pre-processing steps will make the process a multi-product biorefinery. The C1 and C2 gases generated from different industries could also be utilized by various microbes, and this will help to control global warming. The review seeks to expand expertise about the potential application through several perspectives, factors influencing remediation, issues, and prospects.